1970
DOI: 10.1159/000121900
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Multiple Unit Activity of the Brain During the Estrous Cycle

Abstract: Electrical activity of the brain during the critical period in the rat was examined throughout the estrous cycle, using chronically implanted macro-micro electrodes. Slight circadian rhythms were observed in the basal level of the integrated multiple unit activity (MUA) in the basal hypothalamus and forebrain limbic area. In addition to these changes, a gradual increase of MUA in the basal hypothalamus was observed during the evening of diestrus day 2, while there was no change in the forebrain limbic preoptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
2

Year Published

1970
1970
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(62 citation statements)
references
References 0 publications
5
55
0
2
Order By: Relevance
“…It has been well substantiated that these hormones are liberated when a neural surge occurs. And after intravenous injections of LH , FSH and subcutaneous injection of progesterone under the estrogen base (Terasawa and Sawyer, 1970;Kawakami et al, 1971) increases of MUA with latency of 15 to 45 min lasting 2 to 3 hr were observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well substantiated that these hormones are liberated when a neural surge occurs. And after intravenous injections of LH , FSH and subcutaneous injection of progesterone under the estrogen base (Terasawa and Sawyer, 1970;Kawakami et al, 1971) increases of MUA with latency of 15 to 45 min lasting 2 to 3 hr were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, applying the anesthesia at different times of day throughout the estrous cycle, Okamoto et al, (1972) have clarified that the ovulation is delayed by one day when the anesthesia is given at a limited time band (1200-1600) of any day in the cycle except the day of estrus. In this connection, Kawakami et al (1970) have found an increase of polyneuronic activity in the arcuate neucleus of the hypothalamus from 1300 to 1700 every afternoon in the cycling rat. These findings are suggestive of the existence of periodical excitation in CNS which may correlate with some daily rhythmic change for hypothalamo-hypophysial activity concerning gonadotrophin secretions during the cycle.…”
mentioning
confidence: 80%
“…15 In adult experimental animals, the thresholds of limbic seizures in female rats fluctuate during the estrus cycle inversely to serum estradiol levels. 16 Physiological doses of estradiol activate spike discharges 5,6,17,18 and lower the thresholds of seizures induced by electroshock, kindling, pentylenetetrazol, kainic acid, ethyl chloride, and other agents and procedures. [17][18][19][20][21][22] In rabbits, topical brain application, as well as intravenous systemic administration, of estradiol produces a significant increase in spontaneous electrically recorded paroxysmal spike discharges.…”
Section: Estradiolmentioning
confidence: 99%